Analisis Kebutuhan E-Modul Biologi Terintegrasi Nilai IMTAQ Di SMA Negeri 1 Rangsang Barat - Helen Fitria; Siti Robiah (Pusat riset dan Inovasi Nasional, 2024)
Material learning is a tool for conveying teaching material or messages used by an educator, where in the current era teaching media has developed and is very easy to find in other media. One of the teaching media such as E-Module, E-Module which is integrated with IMTAQ values is not often found, therefore researchers are researching this matter which has a research objective, namely for a preliminary study to see how the learning process is and what media are used during the process. learning. The method used in this research is descriptive qualitative where the researcher describes or analyzes the research results obtained. From the results of the research, researchers found that teaching media is really needed in the learning process, which can influence whether students will focus or not during the learning process, as well as whether or not the material messages that educators want to achieve in the ongoing learning process are conveyed. And the teaching media used is still PPT (Powerpoint), where researchers see that there are still many students who lack focus during the learning process, even when educators use teaching media such as PPT (Powerpoint).